TAX-CUSTOMS TERMS BORROWED FROM FARSI-TAJIK LANGUAGE (Scientific journal of the Fergana State University, 2023)
This article briefly discusses the development of Uzbek tax and customs terms, borrowed from the Persian-Tajik language. There are also comments on the role of terminology in the economic life of society.